2012
DOI: 10.1029/2012gc004122
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the offshore extension of the Great Sumatran fault, NW Sumatra, from marine geophysical studies

Abstract: [1] Over the last 20 years, the Great Sumatran Fault (GSF) has been studied on land, but we have very little information about its offshore extension NW of Sumatra and its link with the West Andaman Fault to the north. The problem is further complicated by its vicinity to the volcanic arc. Here we present detailed analyses of the offshore extension of the GSF based on recently acquired high-resolution bathymetry, multichannel seismic reflection data and some old single channel seismic reflection data. Our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 74 publications
2
31
1
3
Order By: Relevance
“…On the other hand, Quaternary sediments primarily consist of sag fill deposits in the AFB. Our interpretation has brought out a stratigraphic framework within the AFB, which compliments similar studies (e.g., Ghosal et al 2012;Singh et al 2013;Moeremans and Singh 2015) published from the southern segment of the Andaman-Sumatra subduction system. The accretionary prism in the region contains several weak zones that could be potential rupture targets in the event of large earthquakes.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Quaternary sediments primarily consist of sag fill deposits in the AFB. Our interpretation has brought out a stratigraphic framework within the AFB, which compliments similar studies (e.g., Ghosal et al 2012;Singh et al 2013;Moeremans and Singh 2015) published from the southern segment of the Andaman-Sumatra subduction system. The accretionary prism in the region contains several weak zones that could be potential rupture targets in the event of large earthquakes.…”
Section: Resultssupporting
confidence: 87%
“…The relocation of the volcanic arc from the Megui ridge ( Fig. 1) further west finally led to the extension in the Megui Basin in the late Oligocene (Ghosal et al 2012;Moeremans and Singh 2015). The entire Andaman Basin is * 1200 km long and extends from the Irrawaddy delta coast of Myanmar in the north to the Sunda trench in the south with a maximum E-W stretch of * 600 km (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…As it enters the Andaman Sea near Banda Aceh, the Great Sumatra Fault divides into two strands: the Aceh fault in the west and the Seulimeum fault in the east. Ghosal et al (2012) have found that the Aceh strand is the most seismically active branch. The strike of these faults is the same as that of the GSF, that is, NW.…”
Section: The Andaman -Nicobar Faultmentioning
confidence: 99%
“…Ghosal et al . [] suggest that this arc shifts farther northward in a pull‐apart basin whereas the main active strand of the GSF follows the Aceh Fault strand.…”
Section: Tectonic Settingmentioning
confidence: 99%